Isotopic analysis of otolith carbonates using laser heating: A fast method for obtaining high‐resolution climate signal. (3rd March 2022) - Sengupta, Torsa; Ghoshmaulik, Sangbaran; Bhattacharya, Sourendra Kumar; Deshpande Mukherjee, Arati; Krishna, Sanjay; Sarkar, Anindya
Abstract : Rationale: The stable isotopic compositions of biogenic carbonates like fish otoliths (ear bones) are widely used for palaeoclimatic reconstruction. The conventional method using acid‐digestion of micro‐milled samples is a multi‐step time‐consuming process. Here we report a fast method based on laser heating of otolith carbonates to obtain accurate and high‐resolution stable isotopic compositions. Method: Otoliths of catfish from the Gulf of Kutch were analysed to check the precision, accuracy and time‐resolution of the isotope ratios. The CO2, generated by heating otoliths with a 50 W CO2 laser, was analysed for its oxygen and carbon isotope ratio [δ 18 O and δ 13 C, with precision: 0.12 and 0.17‰ (1σ), accuracy: 0.13 and 0.25‰, respectively] using a continuous‐flow isotope ratio mass spectrometer. The effect of laser power (0.7–2 W) was assessed for reproducible data. Samples were roasted and analysed to account for the effect of the inherent organic matter on the isotopic values. Results: Roasting did not alter the δ 18 O of the otoliths but increased the δ 13 C slightly. High‐resolution (125 μm) analysis of the right and left otolith of a fish yielded similar δ 18 O and δ 13 C values, suggesting the suitability of either of them for deriving the climate signal. An increase in δ 18 O values from −2‰ to −1‰, observed across the ontogeny, is consistent with the known migratory behaviour of the catfish between freshwater and the sea. Conclusions: The otolith δ 18 O value of an adult fish records the sea surface temperature (with 3°C uncertainty) on a monthly scale. The otolith δ 13 C values, with the knowledge of dietary δ 13 C, provide the mean annual δ 13 C value of dissolved inorganic carbon. The study provides a rapid method for retrieving high‐resolution seasonal climate data from otoliths found aplenty in geological/archaeological records.